The Effect Of Work Ethics On Reinforcing Knowledge Administration in Iraqi National Olympic Committee - Mustafa Hameed Hassan (College of Physical Education and Sport Sciences, 2020)
The researcher studies the effect of work ethics on knowledge administration in the Iraqi national Olympic committee. The research tries to answer questions like what ethics should be concentrated on to develop administration in sports foundations. The researcher studied effects and relationships to conclude that work ethics are excellent in reinforcing knowledge administration in members of the Iraqi national Olympic committee as well as the presence of a significant correlation relationship between work ethics and knowledge administration.